2007
DOI: 10.1007/s00431-006-0367-x
|View full text |Cite
|
Sign up to set email alerts
|

Grommets in otitis media with effusion: the most frequent operation in children. But is it associated with significant complications?

Abstract: It would appear that the complications associated with tympanostomy tube insertion are more frequent than anticipated, reaching 80% of operated ears under specific circumstances and in certain subgroups of children. These complications may resolve with conservative management, but in persistent cases surgical removal of the tubes is mandatory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
1
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 74 publications
1
53
1
4
Order By: Relevance
“…1,9 The risk of TS especially increases in children who had ventilation tubes inserted. 12,23 The clinical observations indicate that the frequency of myringosclerosis is much higher in tympanic membranes with tympanostomy tube insertion than in tympanic membranes with no tympanostomy tube insertion (23-70% and 0-13%, respectively). 5,11,[23][24][25][26][27][28][29][30] It was also observed that the myringosclerosis rate increased with a larger size of tube, several tube insertions and time of tympanostomy tube stay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,9 The risk of TS especially increases in children who had ventilation tubes inserted. 12,23 The clinical observations indicate that the frequency of myringosclerosis is much higher in tympanic membranes with tympanostomy tube insertion than in tympanic membranes with no tympanostomy tube insertion (23-70% and 0-13%, respectively). 5,11,[23][24][25][26][27][28][29][30] It was also observed that the myringosclerosis rate increased with a larger size of tube, several tube insertions and time of tympanostomy tube stay.…”
Section: Discussionmentioning
confidence: 99%
“…12,23 The clinical observations indicate that the frequency of myringosclerosis is much higher in tympanic membranes with tympanostomy tube insertion than in tympanic membranes with no tympanostomy tube insertion (23-70% and 0-13%, respectively). 5,11,[23][24][25][26][27][28][29][30] It was also observed that the myringosclerosis rate increased with a larger size of tube, several tube insertions and time of tympanostomy tube stay. 25,29,31,32 Based on computer modeling, it has been shown that ventilation tube insertion induces shear stress in the structure of the tympanic membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Cholesteatoma (the abnormal collection of skin cells) formation was not included as a complication of OME because previous investigators among many others suggested that VT insertion can avert sequelae of OME such as cholesteatoma formation. 11,128,130,131 Although there may be a chance of calcium deposition within the eardrum with subsequent increased eardrum rigidity (tympanosclerosis) that could be either due to AOM, 132 OME itself 133 or VT insertion. 134 Therefore no incidence of tympanosclerosis formation was predicted as part of any of the strategies included in this analysis given that the actual cause of tympanosclerosis is not fully understood.…”
Section: Ventilation Tubes Strategymentioning
confidence: 99%
“…childhood and the primary reason for children to visit a physician (Freid et al, 1998;Plasschaert et al, 2006). Furthermore, in many countries, AOM is the most common reason for prescribing antibiotics (Gonzales et al, 2001;Leibovitz, 2003;Pichichero, 2000;Plasschaert et al, 2006) or for undergoing surgery (for the placement of grommets) (Vlastarakos et al, 2007). The most common bacterial species cultured from the nasopharynx of children during otitis media episodes are Streptococcus pneumoniae, Haemophilus influenzae, M. catarrhalis and Staphylococcus aureus, either as single pathogens or as co-cultures (Berner et al, 1996;Pettigrew et al, 2008), with the patterns of nasopharyngeal colonization by micro-organisms being important determinants for otitis media disease (Faden et al, 1991(Faden et al, , 1997Murphy & Parameswaran, 2009).…”
mentioning
confidence: 99%